2018
DOI: 10.1002/jlcr.3570
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent aryliodine compounds as precursors for radiofluorination

Abstract: Over the last 2 decades or so, hypervalent iodine compounds, such as diaryliodonium salts and aryliodonium ylides, have emerged as useful precursors for labeling homoarenes and heteroarenes with no-carrier-added cyclotron-produced [ F]fluoride ion (t = 109.8 min). They permit rapid and effective radiofluorination at electron-rich as well as electron-deficient aryl rings, and often with unrestricted choice of ring position. Consequently, hypervalent aryliodine compounds have found special utility as precursors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 142 publications
(378 reference statements)
0
30
0
2
Order By: Relevance
“…B. Toluol) hinzugefügt, was hilfreich war, um Nebenreaktionen wie internen Elektronentransfer oder die Disproportionierung der Diaryliodoniumsalze zu verhindern. Die neue Methode wurde für die Synthese verschiedener 18 F‐Pharmazeutika verwendet, darunter [ 18 F]FDOPA, [ 18 F]mFBG, [ 18 F]FDA und [ 18 F]Flutemetamol.…”
Section: Markierungsmethoden Mit Fluor‐18unclassified
See 1 more Smart Citation
“…B. Toluol) hinzugefügt, was hilfreich war, um Nebenreaktionen wie internen Elektronentransfer oder die Disproportionierung der Diaryliodoniumsalze zu verhindern. Die neue Methode wurde für die Synthese verschiedener 18 F‐Pharmazeutika verwendet, darunter [ 18 F]FDOPA, [ 18 F]mFBG, [ 18 F]FDA und [ 18 F]Flutemetamol.…”
Section: Markierungsmethoden Mit Fluor‐18unclassified
“…Insgesamt wurde die Diaryliodoniumsalz‐Methode dank ihrer hohen Effizienz in der 18 F‐Markierung von Arenen – und insbesondere bei Substraten ohne geeignete aktivierende Substituenten – für die Synthese eines breiten Spektrums von klinisch relevanten PET‐Tracern verwendet (Schema C) …”
Section: Markierungsmethoden Mit Fluor‐18unclassified
“…Whereas the two aryl groups could rapidly exchange their positions through aBerry pseudorotation process,the sterically bulky ortho-substituted aryl group was situated in an equatorial position to minimize the steric repulsion, thereby leading to af avored reductive elimination pathway to form aC (sp 2 )À 18 Fb ond with the equatorial arene in both the monomeric and oligomeric states. toluene) was then added for reductive radiofluorination, which was beneficial for inhibiting side reactions,i ncluding internal electron transfer and disproportionation of diaryliodonium salts.T he new method has been used in the synthesis of several 18 Fpharmaceuticals, [126] In 2014, Scott, Sanford, and co-workers reported the Cumediated 18 F-fluorination of mesityl(aryl)iodonium salts (Scheme 22 A). [125] In this approach, diaryliodonium triflate and [ 18 F]fluoride were first dissolved in ap olar aprotic solvent (e.g.…”
Section: F-fluorination Of Hypervalent Iodine(iii) Compoundsmentioning
confidence: 99%
“…[126] Among the methods for the 18 F-labeling of hypervalent iodine(III) species,l ittle attention was paid to other types of l 3 -iodine compounds until the radiofluorination of (diacetoxyiodo)arenes [130] and aryliodonium ylides were developed in recent years.N otably,t he latter method has shown excellent progress in achieving the unprecedented radiofluorination of non-activated arenes. [126] Among the methods for the 18 F-labeling of hypervalent iodine(III) species,l ittle attention was paid to other types of l 3 -iodine compounds until the radiofluorination of (diacetoxyiodo)arenes [130] and aryliodonium ylides were developed in recent years.N otably,t he latter method has shown excellent progress in achieving the unprecedented radiofluorination of non-activated arenes.…”
Section: F-fluorination Of Hypervalent Iodine(iii) Compoundsmentioning
confidence: 99%
“…It was convincingly shown that the three-step process was much easier and reliable to be automated, providing a RCY of 20 ± 1% within 114 min. The iodonium strategy (method ii), which was for the first time introduced into 18 Fradiochemistry in 1995 [108,138,139], and the use of triarylsulfonium salts [140] were initially limited to the synthesis of small molecules, like 1-bromo-4-[ 18 F]fluorobenzene [141] and 1-[ 18 F]fluoro-4-iodobenzene [142,143]. The latter served especially as building blocks in transition metal-mediated reactions for the synthesis of 18 F-radiotracers [128,144].…”
Section: Progress In Aromatic Nucleophilic 18 F-fluorinationmentioning
confidence: 99%